2000
DOI: 10.1116/1.1327300
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and adhesion improvement of Ag deposited on Pa-n by oxygen plasma treatment

Abstract: Articles you may be interested inEffects and thermal stability of hydrogen microwave plasma treatment on tetrahedral amorphous carbon films by in situ ultraviolet photoelectron spectroscopy Parylene-n (Pa-n) and silver are being studied for ultralarge scale integrated circuits because of their favorable properties. These include low dielectric constant ͑2.65͒, negligible water take-up, chemical inertness, low temperature deposition, as well as compatibility with current integrated circuits manufacturing for Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Silver was selected as a potential interconnect material, for its low bulk electric resistivity 17,18 ; hence, the resistivity of the Cu alloy remains low once the silver nitrite has dissociated during annealing at high temperatures. Sieradzki et al 19 report that the resistance of a silver thin film deposited on an SiO 2 substrate is a function of the annealing time.…”
Section: Introductionmentioning
confidence: 99%
“…Silver was selected as a potential interconnect material, for its low bulk electric resistivity 17,18 ; hence, the resistivity of the Cu alloy remains low once the silver nitrite has dissociated during annealing at high temperatures. Sieradzki et al 19 report that the resistance of a silver thin film deposited on an SiO 2 substrate is a function of the annealing time.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Surface modification of polymers has been thoroughly investigated over the past two decades, with techniques including mechanical treatments, wet-chemical treatments, and plasma treatments. [12] Plasma treatment of parylene has recently been investigated using microwave NH 3 treatment, [13] O 2 plasma treatment, [14,15] and atmospheric plasma treatment. [16] In addition, Riley et al examined Ar/O 2 plasma treatments to improve the adhesion between parylene and a variety of metal and dielectric substrates.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that parylene typically demonstrates poor adhesion toward vapor‐deposited metal electrodes 4, 12–15. Several methods have been used to increase adhesion, including application of A‐174 adhesion promoter,4 plasma treatment,12 and the use of glow‐discharge polymerized methane as a primer 13–15. Another common method of surface modification of parylene involves photooxidation; however, this leads to increased brittleness of the film.…”
Section: Resultsmentioning
confidence: 99%
“…Although parylene has many desirable characteristics, the fact that it is inert can limit its usefulness in a range of applications. Many metals do not adhere strongly to the bare parylene surface,12–15 and the inertness of the material might cause tissue reactivity and encapsulation, affecting the use of the material in biomedical implants both as a protective and as an interfacial material 16. Chemical functionality has been incorporated into parylene films by adding functional groups to the dimer before chemical vapor deposition 17.…”
Section: Introductionmentioning
confidence: 99%